Final answer:
To make the expressions 3d−4 and 12d÷6 equivalent, the value of d is 4.
Step-by-step explanation:
To find the value of d that makes the expressions 3d−4 and 12d÷6 equivalent, we need to set the two expressions equal to each other and solve for d.
3d−4 = 12d÷6
To simplify the equation, we can multiply both sides by 6 to eliminate the fraction:
6(3d−4) = 6(12d÷6)
18d−24 = 12d
Next, we can subtract 12d from both sides:
18d−12d−24 = 12d−12d
6d−24 = 0
Finally, we can add 24 to both sides:
6d−24+24 = 0+24
6d = 24
To isolate d, we divide both sides by 6:
6d÷6 = 24÷6
d = 4